The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep26034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tunable Band Gap Semiconductor Nickel Sulphide Nanoparticles: Rapid and Round the Clock Degradation of Organic Dyes

Abstract: Controlled shape and size with tuneable band gap (1.92–2.41 eV), nickel sulphide NPs was achieved in presence of thiourea or thioacetamide as sulphur sources with the variations of temperature and capping agents. Synthesized NPs were fully characterized by powder XRD, IR, UV-vis, DRS, FE-SEM, TEM, EDX, XPS, TGA and BET. Capping agent, temperature and sulphur sources have significant role in controlling the band gaps, morphology and surface area of NPs. The catalytic activities of NPs were tested for round the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 61 publications
6
47
0
Order By: Relevance
“…The incorporation of NiO and NiS into the Fe 3 O 4 @PPY support inhibited the charge carrier transition and recombination of electron/hole leading to lower photoluminescence emission. Similar results were reported by Habibi‐Yongjeh who studied photoluminescence of nanocomposites and reported that by incorporation of g‐C 3 N 4 into Ag 2 SO 4 and Fe 3 O 4 /AgI/Ag 2 CrO 4 nanocomposite, the photoluminescence intensity of g‐C 3 N 4 was significantly decreased.…”
Section: Resultssupporting
confidence: 89%
“…The incorporation of NiO and NiS into the Fe 3 O 4 @PPY support inhibited the charge carrier transition and recombination of electron/hole leading to lower photoluminescence emission. Similar results were reported by Habibi‐Yongjeh who studied photoluminescence of nanocomposites and reported that by incorporation of g‐C 3 N 4 into Ag 2 SO 4 and Fe 3 O 4 /AgI/Ag 2 CrO 4 nanocomposite, the photoluminescence intensity of g‐C 3 N 4 was significantly decreased.…”
Section: Resultssupporting
confidence: 89%
“…Ag-In-Ni-S nanocomposites with a W 2 /W 1 value of 0.0022 degraded 98% MB in 12 min41. NiS nanoparticles with a W 2 /W 1 value of 0.0089 degraded 100% MB in 15 min42. CuS caved superstructure with a W 2 /W 1 value of 0.01 degraded 100% MB in 15 min with the help of hydrogen peroxide43.…”
Section: Resultsmentioning
confidence: 99%
“…Significant resultsf rom the photoinduced electron-storage mechanisms further led to the development of new and modified systems, such as TiO 2Àx N x /NiO bilayer thin films, [34] WO 3 , [35] TiO 2 -SWCNT (SWCNT = single-walled carbon nanotubes), [36] AgÀTiO 2 , [37] PtÀWO 3 ,C u II ÀWO 3 , [38] Ni(OH) 2 -coupled N-doped TiO 2 ,F e II ÀTiO 2 ,C u II ÀWO 3 ,P t ÀWO 3 , [39] hydrogen-treated PtÀ WO 3 , [40] Cu 2 O/TiO 2 , [41] AgÀInÀNiÀSn anocomposites, [42] H:PtÀ WO 3 /TiO 2 ÀAu nanospheres, [43] TiO 2 /SiO 2 /MnO x , [44] SnO 2 -decorated Cu 2 O, [45] TiO 2 ÀNiO/TiO 2 film, [46] graphitic carbon nitride (g-C 3 N 4 )/carbon nanotubes (CNTs)/graphene (Gr), [47] modified carbon nitride, [48] AuÀZnO, [49] Pt-loaded TiO 2 /CeO 2 /SiO 2 [50] AgÀ ZnO, [51] NÀTiO 2 , [52] metal-organic frameworks on Au/TiO 2 , [53] nickel sulfide, [54] Ag-modified PCs, [55] ZnO 2 /polypyrrole, [56] and Rh/Au-modified Al 2 O 3 , [57] and studied for their day-nightp hotocatalytic properties, as discussed in the following sections.…”
Section: Prospective Materialsmentioning
confidence: 99%